Progress toward understanding chromosome silencing by Xist RNA - Brockdorff, Neil (Genes Dev, 2020)
The X inactive-specific transcript (Xist) gene is the master regulator of X chromosome inactivation in mammals. Xist produces a long noncoding (lnc)RNA that accumulates over the entire length of the chromosome from which it is transcribed, recruiting factors to modify underlying chromatin and silence X-linked genes in cis. Recent years have seen significant progress in identifying important functional elements in Xist RNA, their associated RNA-binding proteins (RBPs), and the downstream pathways for chromatin modification and gene silencing. In this review, we summarize progress in understanding both how these pathways function in Xist-mediated silencing and the complex interplay between them.